Estimation of multivariate volatility spillover effects model of Philippine producer-consumer pork, chicken, and milkfish prices, 1990-2013 - Delfin-Villanueva, Maritess (Passage Journal, 2016)
This time-series study investigated causality using Granger causation, cointegration and volatility spillover effects ("heat waves" and "meteor shower" effects) between producer and consumer prices of chicken, pork, and milkfish markets in the Philippines, and among different consumer prices using the methodology of Generalized Autoregressive Conditional Heteroscedastic (GARCH). GARCH model estimation was done using 18-year monthly data (from January 1990 to December 2007) for each commodity under study. A total of 66 monthly observations (from January 2008 to June 2013) was done in forecasting to test the formulated models.